2022
DOI: 10.1186/s40478-022-01329-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar morphometric and spectroscopic biomarkers for Machado-Joseph Disease

Abstract: Machado-Joseph disease (MJD) or Spinocerebellar ataxia type 3 (SCA3) is the most common form of dominant SCA worldwide. Magnetic Resonance Imaging (MRI) and Proton Magnetic Resonance Spectroscopy (1H-MRS) provide promising non-invasive diagnostic and follow-up tools, also serving to evaluate therapies efficacy. However, pre-clinical studies showing relationship between MRI-MRS based biomarkers and functional performance are missing, which hampers an efficient clinical translation of therapeutics. This study as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 50 publications
2
19
2
Order By: Relevance
“…Interestingly, we observed no correlation between NfL and tNAA or myo-Ins, markers of neuronal health and glial contributions, respectively. MRS studies in patients with SCA3 (Miranda et al, 2022, Adanyeguh et al, 2015 and SCA3 mice (Miranda et al, 2022) have revealed significant increases in myo-Ins, however these were specifically observed during early-stage disease in mice, in contrast to our aged Q84 mice. Decreased tNAA has been demonstrated in multiple neurodegenerative diseases (Adanyeguh et al, 2015) including SCA3 (Chandrasekaran et al, Miranda et al, 2022) and is classified as a marker of neuronal and axonal degeneration.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Interestingly, we observed no correlation between NfL and tNAA or myo-Ins, markers of neuronal health and glial contributions, respectively. MRS studies in patients with SCA3 (Miranda et al, 2022, Adanyeguh et al, 2015 and SCA3 mice (Miranda et al, 2022) have revealed significant increases in myo-Ins, however these were specifically observed during early-stage disease in mice, in contrast to our aged Q84 mice. Decreased tNAA has been demonstrated in multiple neurodegenerative diseases (Adanyeguh et al, 2015) including SCA3 (Chandrasekaran et al, Miranda et al, 2022) and is classified as a marker of neuronal and axonal degeneration.…”
Section: Discussioncontrasting
confidence: 84%
“…MRS studies in patients with SCA3 (Miranda et al, 2022, Adanyeguh et al, 2015, Chandrasekaran et al) and SCA3 mice (Miranda et al, 2022) have revealed significant increases in myo-Ins, however these were specifically observed during early-stage disease in mice, in contrast to our aged Q84 mice. Decreased tNAA has been demonstrated in multiple neurodegenerative diseases (Adanyeguh et al, 2015) including SCA3 (Chandrasekaran et al, Miranda et al, 2022) and is classified as a marker of neuronal and axonal degeneration. While the cerebellum is a heavily impacted region in SCA3, studies in patients and mice demonstrate additional degeneration of the brainstem, substantia nigra, spinal cord, and thalamus (Rub et al, 2013), which we did not assess via MRS in this study.…”
Section: Discussioncontrasting
confidence: 58%
“…34 MRS conducted in patients with polyglutamine expansion diseases has revealed strong evidence for specific neurochemical abnormalities. 12,13,21,22,32,33,[35][36][37] Longitudinal MRS patient data exist for multiple SCA types in natural history studies relative to age-and sex-matched controls. 38,39 Similar natural history studies have demonstrated motor impairment progression in SCA3 mouse models that exhibit onset of motor deficits as early as 4 weeks of age, with homozygous SCA3 mice exhibiting significantly decreased distance traveled in open field assessments, 40,41 increased duration of beam walking assays, 41 abnormal gait, and hindlimb clasping.…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation focused on the SCA3 mouse cerebellum and brainstem, as prior research demonstrated large structural degeneration and volume decreases within these regions in patients. 4,32,36,37,42 Although the pons and cerebellum have previously been studied via MRS in patients 12,13,15,36 and the cerebellum in SCA3 mouse models, 16,37 to our knowledge, this is the first study to investigate SCA3 mouse brainstem neurochemical abnormalities. Our study reveals specific neurometabolite changes in SCA3 mice, including increased Gln and decreased tNAA and tCho levels in both the brainstem and cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…MRS data were saved as free induction decay (FIDs), corrected for frequency drift and for residual eddy current effects using the water signal. Spectral data quantification (peak concentrations) was performed with LC model software package (Stephen Provencher Inc.) as briefly described in our previous work (Miranda et al, 2022). This tool calculates the best fit to the acquired spectrum as a linear combination of models from a basis set of brain metabolites.…”
Section: Proton Magnetic Resonance Spectroscopy ( 1 H-mrs)mentioning
confidence: 99%